KOMPARASI METODE PERSAMAAN EVAPOTRANSPIRASI DALAM PENENTUAN EVAPOTRANSPIRASI TANAMAN SAWI ( BRASSICA RAPA SUBSP. CHINENSIS) MENGGUNAKAN SISTEM TEROTOMASI PADA DAERAH JATINANGOR - Jaycee Gandeng Junior, Phil
Caisim (Brassica rapa subsp. Chinensis) is a plant require good irrigation management. In the practice of water supply irrigation management, most of time its not precise and accurate. The approach needed to be taken which error to be minimize could be done by designing an automation system. In this study the initial design of an ESP32 – based automated drip irrigation automation system was carried out in real-time and can be checked remotely via Google Firebase devices. The basis of mathematical equations used in this research is the equation Matt – Shuttleworth (T1), Priestley – Taylor with Kc FAO (T2), Priestley – Taylor with Kc Dual Coefficient (T3) against the equation FAO – Penman Monteith Kc FAO with water based on reference data (T4), the reading of the soil moisture with a threshold of 37.96% (T5), and based on the Fuzzy algorithm (T6) . Evaluation of the significance of the mathematical equations and the method of giving water is done by taking data at indoor and outdoor locations (screenhouse).The results of this study indicate the mathematical equation gives the most significant results in biomass production is the Priestley – Taylor equation with Kc Dual – Coefficient and the most efficient water efficiency is achieved by the application of Fuzzy equation ( T6).